Effect of Temperature on Structure and Electrode Properties of LaNi3.8Co0.6Mn0.3M0.3 Hydrogen Storage Alloys. Issue 7 (July 2015) - Si, Li; Huaiying, Zhou; Wenping, Liu; Huaigang, Zhang; Jianqiu, Deng; Zhongmin, Wang
Abstract: A series of experiments have been performed to investigate the temperature effects on the structure and the electrochemical properties of LaNi3.8 Co0.6 Mn0.3 M 0.3 ( M =Ni, Al, Cu) hydrogen storage alloys at different temperatures of 238, 273, 303 and 323 K. Samples A, B and C were used to represent LaNi4.1 Co0.6 Mn0.3 (Ni substituted alloy), LaNi3.8 Co0.6 Mn0.3 Al0.3 (Al substituted alloy) and LaNi3.8 Co0.6 Mn0.3 Cu0.3 (Cu substituted alloy), respectively. The structures and the electrochemical properties of A, B and C hydrogen storage alloys were investigated by XRD and simulated battery test, respectively. The results reveal that all of the alloys are composed of the homogeneous LaNi5 phase with a CaCu5 -type hexagonal structure. The low-temperature properties of the Cu substituted alloy are improved, and the high-temperature discharge capacity of the Al substituted alloy is enhanced. Electrochemical impedance spectroscopy (EIS) analysis shows that the improvement of high-temperature discharge capacity of alloy electrode B is attributed to the formation of dense oxide film to protect the active material from corrosion, which is not favorable to charge-transfer reaction at the interface of electrode-electrolyte. The deterioration in the high-rate dischargeability (HRD) of alloy electrodes B and C are attributed to the degradation of electrochemical kinetics, including both charge-transfer reactions on the electrode surface and hydrogen diffusion in the bulk. Furthermore, the good low-temperature performance of alloy electrode C is due to the improvement of charge-transfer reaction.